2014
DOI: 10.3892/ol.2014.2516
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological analysis of CD8-positive lymphocytes in the tumor parenchyma and stroma of hepatocellular carcinoma

Abstract: Tumor-infiltrating lymphocytes may be a manifestation of antitumor immunity. In the present study, hepatocellular carcinoma (HCC) and pericancerous non-tumor liver tissues samples were obtained from 86 surgical patients who had not received preoperative treatment. The cellular expression levels of CD4 and CD8 were immunohistochemically examined in the two tissue groups using tissue microarrays, to evaluate their clinicopathological relevance. Immunohistochemically, CD4 and CD8 T cells were observed in the tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Moreover, the relationship between inflammation and HCC should be also evaluated because the immune system is important in the tumor microenvironment. For example, it was shown that CD8 expression was significantly increased in the peritumor chronic hepatitis and cirrhotic parenchymas, compared with those in paired tumor parenchymas [19]. This finding is concurrent with the results of a study revealing that the proportion of immunesuppressed regulatory T cells was significantly higher in HCC than that in the nontumorous liver.…”
Section: Do We Need To Study the Nontumorous Histopathologic Features?supporting
confidence: 71%
“…Moreover, the relationship between inflammation and HCC should be also evaluated because the immune system is important in the tumor microenvironment. For example, it was shown that CD8 expression was significantly increased in the peritumor chronic hepatitis and cirrhotic parenchymas, compared with those in paired tumor parenchymas [19]. This finding is concurrent with the results of a study revealing that the proportion of immunesuppressed regulatory T cells was significantly higher in HCC than that in the nontumorous liver.…”
Section: Do We Need To Study the Nontumorous Histopathologic Features?supporting
confidence: 71%
“…The CD4+T/CD8+T ratio is crucial for the immune response and immune regulation; its changes reflect the immune state. 12 , 13 Some studies have found that lower CD8+TILs levels are related to some clinicopathological parameters, such as negative HBsAg, large tumor size, and late TNM stage. In addition, the high-density CD8+TILs have been related to better OS and DFS.…”
Section: Discussionmentioning
confidence: 99%
“…A dramatic fall in the CD4 + T lymphocyte level greatly influenced the anti-tumor activity that may lead to a fast progression of HCC. Second, with the support of perforin and granzyme, CD8 + cytotoxic T lymphocytes (CTLs) can directly contact and kill tumor cells [ 35 ]. There is persuasive evidence that the depletion of CTLs may promote the invasion of tumor cells into the surrounding tissue and metastasis to new body sites; collectively, an increased number of CTLs in HCC is closely connected to a reduced tumor diameter and longer survival times [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%